2023
DOI: 10.7717/peerj.15161
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal habitat complexity influences the density of the non-native crabHemigrapsus sanguineus

Abstract: Habitat structural complexity can provide protection from predators, potentially affecting population density of native and non-native prey. The invasive Asian shore crab, Hemigrapsus sanguineus, occurs in variable densities in the rocky intertidal zone of eastern North America and northern Europe, often in densities greater than in its native range. The present study examined the influence of habitat complexity on the density of H. sanguineus. Artificial shelters of concrete pavers with stones arranged in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Field tethering experiments were conducted in the lower intertidal zone of Clark’s Cove, New Bedford, MA (41°35′40.33″N, 70°54′37.45″W) June 28–August 26, 2020 ( Table 1 ) at +0.29 m above mean low water (average tidal range for the location is 1.1 m). Previous investigations at the study site showed crabs were most abundant at that tidal elevation ( Towne, Judge & O’Connor, 2023 ).…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Field tethering experiments were conducted in the lower intertidal zone of Clark’s Cove, New Bedford, MA (41°35′40.33″N, 70°54′37.45″W) June 28–August 26, 2020 ( Table 1 ) at +0.29 m above mean low water (average tidal range for the location is 1.1 m). Previous investigations at the study site showed crabs were most abundant at that tidal elevation ( Towne, Judge & O’Connor, 2023 ).…”
Section: Methodsmentioning
confidence: 74%
“…Both male and female H. sanguineus are highly mobile and can travel up to 16 m per day ( Brousseau et al, 2002 ). Thought to be most active at high tide, laboratory experiments conducted during daytime found crabs were more likely to move under and out from under shelter when submerged in water ( Towne, Judge & O’Connor, 2023 ). Activity at high tide may expose crabs to visual predators, like T. onitis and T. adspersus , which use a scan-and-pick foraging strategy to feed in the intertidal zone ( Dew, 1976 ; Deacutis, 1982 ) where the crabs occur ( Brousseau et al, 2002 ; Epifanio, 2013 ; Towne, Judge & O’Connor, 2023 ).…”
Section: Discussionmentioning
confidence: 99%